Impact of anxiety and depression on the quality of life of cancer patients: A literature review (Research, Society and Development, 2025)
Cancer remains a major global Public Health challenge and is frequently accompanied by significant psychological distress throughout the disease trajectory. This literature review aimed to examine the relationship between anxiety, depression, and Health-Related Quality Of Life (HRQoL) in cancer patients, focusing on studies published between 2012 and 2019. Searches were conducted in SciELO, LILACS, and BIREME using descriptors related to quality of life, anxiety, depression, and neoplasms. Of the 51 studies initially identified, 12 met the inclusion criteria and were fully analyzed. Findings revealed that anxiety and depression are highly prevalent among cancer patients and are consistently associated with significant impairment in HRQOL, affecting physical, emotional, social, and cognitive domains. Evidence also indicates negative effects on treatment adherence, patient functioning, self-care, and clinical prognosis. Factors such as female sex, younger age, limited social support, chronic pain, and severe fatigue were identified as contributors to increased psychological vulnerability. The literature highlights the need for systematic screening of emotional symptoms and for integrating psychosocial and/or pharmacological interventions into oncology care. Early identification and appropriate management of anxiety and depression are essential to providing comprehensive care, reducing emotional distress, and improving quality of life for individuals living with cancer.